Synthesis and Characterization of a Bis-Pyrazoline Derivative as Corrosion Inhibitor for A283 Carbon Steel in 1M HCl: Electrochemical, Surface, DFT and MD Simulation Studies - Selatnia, I.; Sid, A.; Benahmed, M.; Dammene debbih, O.; Ozturk, T.; Gherraf, N. (Pleiades Publishing Ltd, 2018)
The effect of a new synthesized bis-pyrazoline derivative namely: 5,5'-(1,4-phenylene) bis [1‑formyl-4,5-dihydro-3-phenyl-1H pyrazole] (Bis-Pyr) on carbon steel corrosion in 1M HCl was investigated using weight loss, potentiodynamic polarization and EIS measurement. DFT calculation and molecular dynamics simulation were used to confirm the experimental results. The results showed that inhibition efficiency of the (Bis-Pyr) compound increases with the increase of its concentration and acts as a mixed type inhibitor, e.i affecting both anodic and cathodic reactions. The adsorption of the compound on steel surface is both physical and chemical adsorptions and follows Langmuir isotherm. The surface morphology of the steel surface was carried out by scanning electron microscopy (SEM). The data obtained from theoretical and experimental studies were in reasonable agreement.